Harvesting season in Nyando climate-smart villages - CGIAR Research Program on Climate Change, Agriculture and Food Security (2015)
Nyando climate-smart villages are home to a mix of climate-smart technologies tailored to boost farmers’ ability to adapt to climate change, manage risks and build resilience. These technologies will in turn improve livelihoods and incomes. Photos S.Kilungu (CCAFS).